Analisis Kebijakan Pendidikan Berkelanjutan: Studi Evaluasi atas Tujuh Arah Strategis Pemerintah dalam RPJMN 2020–2024 - Islami, Hani; Rozak, Abdul (Innovative: Journal Of Social Science Research, 2025)
Sustainable education serves as a fundamental pillar in building an inclusive, adaptive, and competitive society in the face of global changes. The Indonesian government addresses these challenges through the seven strategic directions outlined in the 2020–2024 National Medium-Term Development Plan (RPJMN). This article aims to evaluate the effectiveness and implementation of these policy directions as part of national education reform. A descriptive-qualitative approach was employed using policy analysis based on official documents and sectoral policy reviews. The findings reveal that despite the government’s strong commitment to educational transformation, challenges remain in equitable access, teacher quality, curriculum relevance, and cross-sectoral collaboration. The evaluation concludes that the effectiveness of the policy is significantly influenced by consistent planning, sufficient funding, and strong synergy between central and regional governments, along with educational institutions as the primary implementers. Sustainable reform requires a holistic approach and long-term impact orientation to ensure meaningful and measurable progress in the education sector.